Buying and selling “likes” in online business: a Fiqhi analysis - Mat Jubri@Shamsuddin, Mustafa (Faculty of Syariah and Law (FSU), Selangor International Islamic University College (KUIS), 2022)
Among the online business marketing strategies that target the attraction of buyers to the product is their trust about the marketability and effectiveness of the product through the number of likes on social media. This practice is related to several legal issues that need to be refined and addressed through fiqh analysis that investigates the purpose, method and effect of this issue. Thus, this study aims to present this problem thoroughly, then identify the aspects that require fiqh analysis, and then place the parameters that determine the Shariah-compliant standards for this problem. This study relies on qualitative methods through the collection of data from primary and secondary written sources, and depends on the methods of ijtihad and the opinions of scholars in assessing this problem and the rulings that apply to it. Among the findings of this study is that the sale and purchase of likes is bound by the fiqh of sale and purchase of service benefits as the basis of its necessity, while the basis that causes the ban refers to the element of fraud and ambiguity in this transaction.